PENCARIAN OTENTISITAS DIRI KOMUNITAS MUALLAF DI KABUPATEN SORONG PAPUA BARAT - Munawir Haris (Harmoni, 2014)
This study was conducted to explore and understand the factors and the chronology of the religious conversion process in the city and regency of Sorong, Papua. It specifically studies the Muslim converts in the area. This qualitative study uses the phenomenological theory adopted from Hussrel and symbolic interaction theory to explain religious conversion. This study shows that the main factors for conversion from Protestantism to Islam were: spiritual leaders and direct guidance from God. Converts believed that God has opened their hearts and minds to see the truth of Islam. They did not see the obstacles they faced as something difficult, because those factors have strongly penetrated the beleifs of the Abun ethnic group. The chronology of religious conversion had three main stages: 1) personal/individual conversion, 2) inviting their family to Islam after moving from Sorong regency, but also hiding their new identity--even for several years and finally, 3) openly dharing that they had converted to Islam.